New approaches to the study of biblical interpretation in Judaism of the Second Temple period and in early Christianity : proceedings of the Eleventh International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, jointly sponsored by the Hebrew University Center for the Study of Christianity, 9-11 January, 2007 - Anderson, Gary A., 1955-; Clements, Ruth.; Satran, David. (Studies on the Texts of the Desert of Judah, 2013)
2007 marked the 60th anniversary of the discovery of the first Dead Sea Scrolls. The 11th International Orion Symposium (January, 2007), "New Approaches to the Study of Biblical Interpretation in the Second Temple Period and in Early Christianity," provided a measure of the ways in which the discovery of the scrolls has altered the paradigms for textual and historical studies in the intervening six decades. The papers in this volume address such issues as the connections and distinctions between Jewish interpretation within the Land of Israel and outside of it; between Jewish and Christian exegesis in earlier and later periods; between biblical interpretation in literature and in art; between interpretation and the formation of the biblical canon.